Flame-retardant Cotton Fabric Through Graft Copolymerisation - Kaur, Inderjeet; Rajneesh, Ms.; Vibha, Dr. (Defence Science Journal, 2007)
In an attempt to impart flame-retarding properties to the cotton fabric, post-graftingphosphorylation reactions on grafted cotton fabric were carried out. Photochemical graftcopolymerisation of 4-vinyl pyridine (4-VP) onto cotton fabric using benzophenone asphotosensitiser was carried out. Maximum percentage of grafting Pg, (18.50 %) was obtainedunder optimum conditions; irradiation time 75 min, 0.5 ml of benzophenone, [4-VP]=748.71 x10-2 mole/l and 5 ml of water in the reaction mixture. Aliphatic alcohols of varying chain lengthdecreased percentage of grafting. The pendant pyridine rings of the 4-VP grafted cotton fabricwere converted to pyridinium chloride followed by the reaction with acrylamide to give 2-amido-ethylpyridiniumchloride. This was subjected to phosphorylation reaction with PCl3/petroleumether. The phosphorylated grafted cotton fabric burns only in the presence of flame with veryslow propagation of the flame (only 3.8 cm2) was found to burn of the total area of 147 cm2 with0.12 g of the ash content. Characterisation of gray cotton fabric and modified cotton fabric wascarried out by FTIR, thermogravimetric analysis, crease recovery, and moisture absorption studies.